Melatonin Ameliorates Axonal Hypomyelination of Periventricular White Matter by Transforming A1 to A2 Astrocyte via JAK2/STAT3 Pathway in Septic Neonatal Rats - Jiang S; Wang H; Zhou Q; Li Q; Liu N; Li Z; Chen C; Deng Y (Dove Medical Press, 2021)
Shuqi Jiang,1,* Huifang Wang,1,2,* Qiuping Zhou,1,3 Qian Li,1,2 Nan Liu,1,3 Zhenggong Li,1 Chunbo Chen,1 Yiyu Deng1,2 1Department of Critical Care Medicine, Guangdong Provincial People's Hospital, Guangdong Academy of Medical Sciences, Guangzhou, 510080, People's Republic of China; 2The Second School of Clinical Medicine, Southern Medical University, Guangzhou, 510515, People's Republic of China; 3Guangdong Provincial People's Hospital, Guangdong Academy of Medical Sciences, School of Medicine, South China University of Technology, Guangzhou, 510641, People's Republic of China*These authors contributed equally to this workCorrespondence: Chunbo Chen; Yiyu Deng Tel +86 20-83827812-60228Fax +86 20-83827712Email gghccm@163.com; yiyudeng666@163.comBackground: Astrocyte A1/A2 phenotypes may play differential role in the pathogenesis of periventricular white matter (PWM) damage in septic postnatal rats. This study aimed to determine whether melatonin (MEL) would improve the axonal hypomyelination through shifting A1 astrocytes towards A2.Methods: One-day-old Sprague-Dawley rats were divided into control, LPS, and LPS+MEL groups. Immunofluorescence was performed to detect C1q, IL-1α, TNF-α, IBA1, GFAP, MAG, C3 and S100A10 immunoreactivity in the PWM of neonatal rats. Electron microscopy was conducted to observe alterations of axonal myelin sheath in the PWM; moreover, myelin protein expression was assessed using in situ hybridization. The effects of MEL on neurological function were evaluated by behavioral tests. In vitro, A1 astrocytes were induced by IL-1α, C1q and TNF-α, and following which the effect of MEL on C3 and S100A10 expression was determined by Western blot and immunofluorescence.Results: At 1 and 3 days after LPS injection, IBA1+ microglia in the PWM were significantly increased in cell numbers which generated excess amounts of IL-1α, TNF-α, and C1q. The number of A1 astrocytes was significantly increased at 7- 28d after LPS injection. In rats given MEL treatment, the number of A1 astrocytes was significantly decreased, but that of A2 astrocytes, PLP+, MBP+ and MAG+ cells was increased. By electron microscopy, ultrastructural features of axonal hypomyelination were attenuated by MEL. Furthermore, MEL improved neurological dysfunction as evaluated by different neurological tests. In vitro, MEL decreased the C3 significantly, and upregulated expression of S100A10 in primary astrocytes subjected to IL-1α, TNF-α and C1q treatment. Importantly, JAK2/STAT3 signaling pathway was found to be involved in modulation of A1/A2 phenotype transformation.Conclusion: MEL effectively alleviates PWMD of septic neonatal rats, which is most likely through modulating astrocyte phenotypic transformation from A1 to A2 via the MT1/JAK2/STAT3 pathway.Keywords: astrocyte, sepsis, melatonin, hypomyelination, neuroprotection